ASUHAN KEBIDANAN PADA BAYI DENGANALERGI SUSU SAPI DI KLINIK ABRAR MEDICAL CENTRE PALOPO - Ny. Asmawati; Ny. Maryati (Voice of Midwifery, 2016)
The incidence of allergic disease in children has been increasing in the last 2 decades worldwide, including Indonesia. The increase in the incidence rate is estimated due to lifestyle changes and pollution. Allergic diseases can have a long-term negative impact, thus disrupting the quality of a child's life and disrupting the growth process. In various regions of Indonesia, the incidence of allergies varies from 30% to 60%.This research uses quantitative research explanation with case study method approach.The results of this case study where all action plans have been implemented ie in this case encourage the mother to continue breastfeeding to her child and stop giving formula milk. Cow milk allergy in infants can bertatasai by collaborating with dr. Children in terms of drug delivery and care provided. Keywords : Baby, Cow's milk allergy